Initial Experience with Laparoendoscopic Single-Site Surgery by Use of a Homemade Transumbilical Port in Urology - Lee, Seok Young (The Korean Urological Association, 2010)
PURPOSE: We present our initial experience with laparoendoscopic single-site surgery (LESS) by a single surgeon in the urologic field. MATERIALS AND METHODS: From May 2009 to April 2010, 30 consecutive patients underwent LESS including seven cases of nephrectomy, five cases of nephroureterectomy with bladder cuff excision, four cases of ureterolithotomy, eight cases of marsupialization, and six cases of varicocelectomy. We performed a retrospective analysis of the medical records of the above patients. The single port was made with a surgical glove and an Alexis® wound retractor (Applied Medical, Rancho Santa Margarita, CA, USA). The wound retractor was put into the peritoneal space through an umbilical incision, and a laparoscopic triangle was secured by crossing both instruments. All operations were performed by the transperitoneal approach. RESULTS: Mean patient age was 54.8 years. Mean operative time was 171.2±109.1 minutes. Mean estimated blood loss was 265.0±395.5 ml. Mean incision length was 3.2±1.4 cm. Mean length of hospitalization was 5.2±2.9 days. There was one laparoscopic conversion and two open conversions. There were two cases of transient ileus that improved with conservative treatment. Mean visual analogue pain scales on the operative day and first postoperative day were 6.3/10 and 3.1/10, respectively. CONCLUSIONS: In our experience, LESS for urologic surgery is feasible, safe, and clinically applicable. We consider the homemade single-port device to be a relatively cost-effective and convenient device. If surgical instruments for LESS and appropriate ports specified for LESS are developed, LESS would be a surgical treatment technique that could be used as an alternative to the conventional types of laparoscopic surgery.